Gender-specific difference of clinical and plaque characteristics in myocardial infarction with non-obstructive artery (MINOCA): insights from optical coherence tomography. (14th October 2021) - Zeng, M; Hu, S; Meng, W; Zhao, C; Wang, S; Weng, Z; He, L; Qin, Y; Feng, X; Chen, X; Xu, Y; Yi, B; et al.
Abstract: Background: To date, sparse data are available with regard to gender differences in coronary plaque morphology and composition as underlying mechanism of MINOCA. Purpose: To assess the differences in coronary plaque morphology in culprit lesion between women and men with MINOCA using intravascular optical coherence tomography. Methods: Totally, 7404 consecutives acute myocardial infarction patients who underwent emergency coronary angiography between 2016 and 2019 were screened. MINOCA were identified in 292 patients (mean age: 72.6% male, 54.1% with ST-segment elevation). Optical coherence tomography was performed in 190 patients (men, n=142). Results: Women with MINOCA were older (62.5±10.6 vs. 54.0±11.5, P<0.001) and more over 55 years (75.3% vs. 43.6%, P<0.001). Although women with MINOCA more frequently presented with NSTEMI (56.8% vs. 41.7%, P=0.025) and prior coronary artery disease (CAD) (33.3% vs. 6.3%, P<0.001), they were less likely smoker (27.2% vs. 58.8%, P<0.001). There was no significant difference in incidence of plaque rupture, erosion and calcified nodule between men and women. However, women were more likely to have thin-cap fibroatheroma (TCFA) (39.6% vs. 22.5%, P=0.025). Conclusion: Women with MINOCA were older, more frequently presented with NSTEMI and less smoking compared to men. Besides, more TCFA were observed in women. FUNDunding Acknowledgement: Type of funding sources: None.